Effect of Plasticizer Type on Properties, Structure and Application Effect of Pullulan-Soluble Soybean Polysaccharide Film - Fan ZHAO; Lijun JIANG; Shuangdie LI; Chenyu WANG; Di SUN; Yu LIU; Wei JIANG (Shipin gongye ke-ji, 2025)
In order to improve the flexibility and heat-sealing performance of pullulan-soluble soybean polysaccharide film and its application potential, the effects of four plasticizers (polyethylene glycol, propylene glycol, glycerol and sorbitol) on the physical properties, structure and application effect of pullulan-soluble soybean polysaccharide film were studied in this article. Compared to the pullulan-soluble soybean polysaccharide film without plasticizer, the film with plasticizer showed increase in thickness, moisture content and elongation at break, and decrease in brightness (P<0.05). The propylene glycol, glycerol, and sorbitol films had smooth surfaces and uniform, compact structures. The polyethylene glycol film had a rough surface and porous structure, with a significant decrease in light transmittance and heat-sealing strength (P<0.05). The propylene glycol film showed a decrease in water contact angle, but no significant changes in light transmittance, dissolution time, and heat-sealing strength were observed. The glycerol and sorbitol films showed a higher elongation at break than other films, with a significantly decrease in water contact angle and dissolution time (P<0.05) and a significantly increase in heat-sealing strength (P<0.05). The results of the peptide powder packaging application indicated that the glycerol film showed the best heat-sealing form and instant effect. In summary, glycerol film exhibits good solubility (dissolution time<30 s), high flexibility (high elongation at break), and significant higher heat-sealing strength (2.58 N/15 mm) (P<0.05) compared to other films, and has potential applications as a heat-sealing instant film.